2021
DOI: 10.26599/bsa.2021.9050013
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal resting-state functional connectivity with the mPFC and DLPFC moderates and mediates the association between education level and memory function in subjective cognitive decline

Abstract: Objective: This study aims to determine the relationship between education level, memory function, and hippocampus functional and structural alterations in subjective cognitive decline (SCD). Methods: Seventy-five participants with SCD were divided into high education (HE) and low education (LE) level groups. A Wechsler Memory Scale–Chinese Revision test and functional and structural MRI were performed within 1 week after participant recruitment. The bilateral hippocampus resting-state functional connectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The observed fluctuations in network topology during the break were likely to be directly related to ongoing cognitive processing (Shine and Poldrack, 2018). The current research on RSNs showed that the functional couplings between regions at resting state contained information relevant to cognition, perception, and behavior (Sadaghiani and Kleinschmidt, 2013), rather than simply reflecting an invariant structural anatomy, historical coactivation patterns, or internal dynamics of local areas; the intrinsic activity predicted subsequent perceptual processing (van den Berg et al, 2016;Xu et al, 2021).…”
Section: The High Synchrony Of the Resting State High-order Cognitive...mentioning
confidence: 70%
“…The observed fluctuations in network topology during the break were likely to be directly related to ongoing cognitive processing (Shine and Poldrack, 2018). The current research on RSNs showed that the functional couplings between regions at resting state contained information relevant to cognition, perception, and behavior (Sadaghiani and Kleinschmidt, 2013), rather than simply reflecting an invariant structural anatomy, historical coactivation patterns, or internal dynamics of local areas; the intrinsic activity predicted subsequent perceptual processing (van den Berg et al, 2016;Xu et al, 2021).…”
Section: The High Synchrony Of the Resting State High-order Cognitive...mentioning
confidence: 70%
“…Neuroimaging studies of episodic memory have long shown prefrontal activity associated with episodic retrieval [1,78,79]. The DLPFC has been associated with different aspects of retrieval including being in a retrieval mode [80][81][82], post-retrieval monitoring and evaluation [20,[83][84][85][86], general decision operations [87][88][89], and control-related modulation of the hippocampus [90][91][92]. Much of the fMRI work focusing on understanding the role of the PFC in retrieval has examined the right DLPFC because it showed more robust activation in earlier studies [1,[13][14][15][16][17]80,81], but a meta-analysis of fMRI studies of episodic memory also show the left DLPFC has a role [93].…”
Section: Episodic Memory and The Role Of The Left And Right Prefronta...mentioning
confidence: 99%
“…A previous study has proved that the apolipoprotein E (APOE) ε4 allele is a genetic risk factor for AD, whereas educational attainments have protective effects against cognitive decline in aging and patients with AD (Li et al, 2021 ). Thus, the progression from SCD to MCI and AD may need multidimensional analyses, such as clinical cognitive scales (Tabatabaei-Jafari et al, 2018 ), education level (Xu et al, 2021 ), structural indexes (Moore et al, 2018 ), functional indexes (Sun et al, 2016 ), cerebrospinal fluid (Hays et al, 2018 ), and cortical glucose metabolism measured by positron emission tomography (PET) (Eliassen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%